The Effect of Supplementary Feeding of Lelor Nuggets on Weight Gain of Toddlers with Undernourished Status - Subarkah, Jayanti Tri; Chunaeni, Siti; Arfiana, Arfiana (Poltekkes Kemenkes Semarang, 2024)
Background : The state of the body as a result of food consumption and the utilisation of nutrients as an energy source is known as nutritional status. Protein Energy Deficiency (PEM) continues to be the main cause of nutritional issues in Indonesia generally. In Kedu District, malnutrition was present in 275 instances (7.85%).Methods : PMT biscuits and high-protein lamb nuggets are used in an attempt to raise body weight.By offering intervention group treatment, the kind and design of this research employ a quasi-experimental study design. because two groups—the experimental group and the control group—were compared throughout the course of this study. The study included thirty-two toddlers with both very poor and poor nutritional status as its group. In this study, complete sampling is the sample method used.Result : When the p-value was compared before and after consuming Lor nuggets, the paired T-Test results showed that 0.000 (p≤0.005). Toddlers' weights before and after consuming Lor nuggets for a period of 14 days differed. In children with low nutritional status, lelor nuggets had a stronger influence on weight increase than PMT biscuits, with a mean difference between before and after the intervention of 0.4313 and 0.2438, respectively.Giving kids more food, like lelor nuggets, has the effect of making them heavier if they are malnourished. Toddlers who are malnourished are more likely to gain weight when given extra food along with their lelor nuggets. Body weight (Lelor Nugget Mean 0.4313, Standard Deviation 0.3860) before and after consumption. The body weight mean and standard deviation were 0.2065 and 0.2438, respectively, before and after consuming PMT Biscuits.Conclusions : Supplementary feeding of Lelor Nuggets is more influential in increasing the weight of toddlers with less nutritional status.